Competitiveness and Profitability of Bali Cattle For Farmers in The Southeast Sulawesi Development Center, Indonesia - Gerhana Gerhana; Wiwiek Rindayati; Dominicus Savio Priyarsono (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Bali cattle have a significant role in supporting food security through providing meat and contributing to the economy by increasing farmers’ income. Purpose: This study aimed to analyze the competitiveness and profitability of the Bali cattle business in supporting animal food security and economic growth in Southeast Sulawesi Province. Design/methodology/approach: The study was conducted from June to October 2024 in South Konawe and Muna Regencies, Southeast Sulawesi as centers for Bali cattle development. Data were collected from 240 Bali cattle farmers through direct interviews, focus group discussions, and secondary sources from various agencies. The analysis used in this study was the Policy Analysis Matrix (PAM). Findings/Result: The results of competitiveness in South Konawe Regency were a private cost ratio (PCR) of 0.77 and domestic resource cost (DRC) of 0.82 with a private profitability (PP) of IDR 2.4 million per head per year and social profitability (SP) of IDR 1.9 million per head per year. The competitiveness results in Muna Regency are a private cost ratio (PCR) of 0.52 and domestic resource cost (DRC) of 0.60 with private profitability (PP) of IDR 5.7 million per head per year and social profitability (SP) of IDR 4.8 million per head per year. Conclusion: These results state that the Bali cattle business in both regencies is efficient and has competitiveness both competitively and comparatively. Therefore, developing Bali cattle and farmers' access to input-output prices is crucial in government policies to meet national demand.Originality/value (State of the art): Our research focuses on the competitiveness and profitability of smallholder Bali cattle farming. The study targets farmers utilizing semi-intensive systems (breeding and fattening) or intensive systems (fattening only) in two primary Bali cattle development areas: Konawe Selatan District, representing the mainland, and Muna District, representing the island region in Southeast Sulawesi Province. Keywords: Bali cattle, development centers, competitiveness, profitability, pam